Endodontic Treatment of Fused Teeth with Talon Cusp - Shima Sadat Miri; Hakimeh Ghorbani; Anousheh Rashed Mohassel (Case Reports in Dentistry)
Tooth anomalies are rare phenomena that may be reported by patients as chief complaints or may be discovered by dentists in the oral examination. In a few cases, rare anomalies are found together in one mouth. Decision to treat such anomalies depends on whether or not they interfere with function and esthetics and also the patient's preference. In the present case, a 19-year-old male presented with two right maxillary fused central and lateral incisors and a geminated left maxillary central incisor. A talon-like projection was found at the junction site of the fused teeth. His chief complaint was sensitivity to cold at the site of the giant fused tooth. This report describes the process of diagnosis and treatment of the two anomalies according to patient preference and needs.